Relaxation processes in hard piezoelectric ceramics - Kuzenko, D.V.; Ishchuk, V.M.; Bazhin, A.I.; Spiridonov, N.A. (Functional Materials, 2009)
The results of the relaxation processes investigation in polycrystalline piezoelectric elements after exiting them from the state of the thermodynamic balance under action of AC voltage of the resonance frequency, heating and uniaxial mechanical stresses are presented. The long-time reconstruction of elastic parameters takes place when elements are returned into the initial thermodynamic condition. Observed relaxation is described by the logarithmic function of time. The model, taking into account the polycrystalline structure of ceramics and presence of noncompensated mechanical stresses on crystalline boundaries, is offered for explanation of the observed results.